Shrimp Lipids Inhibit Migration, Epithelial–Mesenchymal Transition, and Cancer Stem Cells via Akt/mTOR/c-Myc Pathway Suppression - Chorpaka Thepthanee; Zin Zin; Soottawat Benjakul; Hongbin Zou; Korrakod Petsri; Bhurichaya Innets; Pithi Chanvorachote (Biomedicines, 2024)
Shrimp is a rich source of bioactive molecules that provide health benefits. However, the high cholesterol content in shrimp oil may pose a risk. We utilized the cholesterol elimination method to obtain cholesterol-free shrimp lipids (CLs) and investigated their anticancer potential, focusing on cancer stem cells (CSCs) and epithelial-to-mesenchymal transition (EMT). Our study focused on CSCs and EMT, as these factors are known to contribute to cancer metastasis. The results showed that treatment with CLs at doses ranging from 0 to 500 µg/mL significantly suppressed the cell migration ability of human lung cancer (H460 and H292) cells, indicating its potential to inhibit cancer metastasis. The CLs at such concentrations did not cause cytotoxicity to normal human keratinocytes. Additionally, CL treatment was found to significantly reduce the levels of Snail, Slug, and Vimentin, which are markers of EMT. Furthermore, we investigated the effect of CLs on CSC-like phenotypes and found that CLs could significantly suppress the formation of a three-dimensional (3D) tumor spheroid in lung cancer cells. Furthermore, CLs induced apoptosis in the CSC-rich population and significantly depleted the levels of CSC markers CD133, CD44, and Sox2. A mechanistic investigation demonstrated that exposing lung cancer cells to CLs downregulated the phosphorylation of Akt and mTOR, as well as c-Myc expression. Based on these findings, we believe that CLs may have beneficial effects on health as they potentially suppress EMT and CSCs, as well as the cancer-potentiating pathway of Akt/mTOR/c-Myc.
Keywords: Polyamine Metabolism and Applications; Echinoderm biology and ecology; Cancer, Stress, Anesthesia, and Immune Response